Postgraduate students’ perspective on supporting “learning from home” to solve the COVID-19 pandemic - Ihsana El Khuluqo; Abdul Rahman A. Ghani; Arum Fatayan (Institute of Advanced Engineering and Science, 2021)
The objective of this present research was to reveal how the postgraduate student perceive of or respond to the online learning process. Quantitative method was adopted in this present research. The results showed that most students who had experienced of the online learning activities encountered some obstacles because they had never conducted Learning From Home (LFH) activities before. The respondents were 428 postgraduate students who actively joined in the LFH activities. There were 316 students used the platform Zoom as the supporting application in the LFH activities. Respondents filled in Google Form, then the collected data could be quickly and accurately processed. Other respondents preferred Google Classroom, WhatsApp and other applications in following the learning activities according to the agreement and features provided in each platform. There were 408 respondents experienced Two-ways communication between the lecturers and the students during the LFH activities. They stated that the limited internet network hindered the online lecturing. There were 31 respondents declared that technology limitations hampered the online lecturing and 105 students revealed that it is the limitations in using the application that caused the online lecturing to become obstacles.